2015
DOI: 10.4314/bcse.v29i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Total phenols and antioxidant activities of natural honeys and propolis collected from different geographical regions of Ethiopia

Abstract: ABSTRACT. In this study, ten honey and five propolis samples from different geographical origins were tested. Both honey and propolis samples showed high content of total phenolic compounds (330-610 mg gallic acid equivalent (GAE)/100 g honey; 365-1022 mg GAE/g ethanol extract of propolis (EEP). The total flavonoids ranged from (15.1-42.6 mg catechin equivalent (CE)/100 g for honey; to 123-74 mg CE/g for EEP. These honeybee products of Ethiopia had high total radical scavenging properties with respect to 2,2-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 33 publications
5
21
0
2
Order By: Relevance
“…Flavanols were hardly researched by spectrophotometric assays. Similar values than ours were obtained for Ethiopian propolis, ranging from 14.76 to 68.88 mg C/g [37] and lower for Thai propolis, with an average of 3.40 mg C/g [38]. Figure 1 shows two chromatograms: (a) corresponds to a mixture of phenolics' standards and (b) to the phenolic profile of one sample from NE-Europe.…”
Section: Total Flavonoids Contentsupporting
confidence: 76%
“…Flavanols were hardly researched by spectrophotometric assays. Similar values than ours were obtained for Ethiopian propolis, ranging from 14.76 to 68.88 mg C/g [37] and lower for Thai propolis, with an average of 3.40 mg C/g [38]. Figure 1 shows two chromatograms: (a) corresponds to a mixture of phenolics' standards and (b) to the phenolic profile of one sample from NE-Europe.…”
Section: Total Flavonoids Contentsupporting
confidence: 76%
“…Ferreira et al (2009) reported that antioxidant values of honey samples changed between 1.63 and 47.62 mg/ml. Total phenol, radical scavenging activity values ranged from 330 to 610 mg GAE/100 g honey and 18.1-59.8%, respectively (Sime, Atlabachew, Redi-Abshiro, & Zewde, 2015). Piljac-Zegarac, Stipcevic, and Belscak (2009) reported that the mean scavenging potential of heterofloral Croatian honey was found as 16.7 mg AAE/ 100 g. Radical scavenging activity values with respect to DPPH of Malaysian honey samples changed between 81.6 and 77.3% (Khalil et al, 2010a;Khalil et al, 2010b).…”
Section: R Esul Ts a N D Discussionmentioning
confidence: 99%
“…Ethiopian honey production accounts for approximately 2.5% of world production and 21.7% of African honey production (Sebeho, 2015). Honey is a natural sweet viscous liquid that honeybees Apis mellifera produce from nectars of flowers, from plant secretions, as well as from excretions of plant sucking insects on the living parts of plants (Tuzen et al, 2007;Saif-ur-Rehman et al, 2008;Nigussie et al, 2012;Nwankwo et al, 2014;Sime et al, 2015;Gul et al, 2015). Honeybees collect these materials, transform by combining with specific substances of their own, deposit, dehydrate, store and leave in the honey comb to ripen and mature (Codex Alimentarius Commission, 2001;Osman et al, 2007;Bibi et al, 2008;Flores et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports on the medicinal importance of honey (Aljadi et al, 2003;Lachman et al, 2010;Nwankw et al, 2014;Pathare et al, 2015;Gul et al, 2015). The major components of honey include various saccharides, water, proteins, vitamins, organic acids, flavonoids, phenolic compounds, inorganic substances, including trace elements and unstable compounds such as enzymes (Bogdanov et al, 2008;Sime et al, 2015;Pathare et al, 2015). If honey is consumed at higher doses of 50 to 80 g per intake, it has a variety of positive nutritional, healing, and prophylactic properties (Bogdanov et al, 2008;Pathare et al, 2015).…”
Section: Introductionmentioning
confidence: 99%